Metagenomic analysis of healthy and diseased peri-implant microbiome under different periodontal conditions: a cross-sectional study - Liang Song; Ziying Feng; Qianrong Zhou; Xingwen Wu; Limin Zhang; Yang Sun; Ruixue Li; Huijuan Chen; Fei Yang; Youcheng Yu (BMC, 2024)
Abstract Background Peri-implantitis is a polybacterial infection that can lead to the failure of dental implant rehabilitation. This study aimed to profile the microbiome of the peri-implant plaque and estimate the effect of periodontitis on it among 40 Chinese participants with dental implant prostheses and presenting with varying peri-implant and periodontal health states. Methods Submucosal plaque samples were collected from four distinct clinical categories based on both their implant and periodontal health status at sampling point. Clinical examinations of dental implant and remaining teeth were carried out. Metagenomic analysis was then performed. Results The microbiome of the peri-implantitis sites differed from that of healthy implant sites, both taxonomically and functionally. Moreover, the predominant species in peri-implantitis sites were slightly affected by the presence of periodontitis. T. forsythia, P. gingivalis, T. denticola, and P. endodontalis were consistently associated with peri-implantitis and inflammatory clinical parameters regardless of the presence of periodontitis. Prevotella spp. and P. endodontalis showed significant differences in the peri-implantitis cohorts under different periodontal conditions. The most distinguishing function between diseased and healthy implants is related to flagellar assembly, which plays an important role in epithelial cell invasion. Conclusions The composition of the peri-implant microbiome varied in the diseased and healthy states of implants and is affected by individual periodontal conditions. Based on their correlations with clinical parameters, certain species are associated with disease and healthy implants. Flagellar assembly may play a vital role in the process of peri-implantitis.